Pelatihan Desain Grafis Menggunakan Aplikasi Canva Untuk Meningkatkan Promosi Produk UMKM - Andi Saehan; Kusmanto; Sudi Suryadi; Tatang Hidayat Pohan (Jurnal Pengabdian Masyarakat Gemilang (JPMG), 2023)
This training aims to provide understanding and skills in using the Canva graphic design application as a tool to enhance MSME product promotion. MSMEs face challenges in communicating their products effectively to potential customers in today's digital era. The Canva application, with its intuitive and various features, can be the right solution to help MSMEs produce attractive and professional promotional materials. This training will cover the basic concepts of graphic design, an understanding of using Canva's design tools, and practice in creating various types of promotional materials, such as posters, banners, flyers, and social media posts. Participants will be invited to develop their creativity and apply effective design elements, such as an attractive layout, the right choice of colors, and a harmonious visual composition. In addition, this training will help participants understand how to adapt designs for various social media platforms, so that promotional messages can be conveyed optimally to the target audience. The concept of using text and images in designs will also be discussed to optimize visual appeal and the message conveyed. In this training, participants will have the opportunity to practice directly by making promotional designs for their own MSME products. This will help them apply the knowledge gained in real situations and get constructive feedback for design improvements. In conclusion, graphic design training using the Canva application has great potential to empower MSMEs in increasing their product promotions. With the knowledge and skills acquired, MSMEs can create promotional materials that are attractive, professional and in accordance with their brand identity. Thus, this training can contribute significantly to expanding market reach and the success of MSMEs in today's digital era.